A ideia dos direitos sociais (Revista Eletrônica Estudos Hegelianos, 2021)
In the US-American reception, Hegel’s conception of sittliche Freiheit is understood as social freedom: Freedom is achieved only socially, i.e. through participation in social institutions. Hegel certainly would not have disagreed with this definition. There is, however, another concept of social freedom in Hegel that needs to be better analyzed. For Hegel, right is the existence (Dasein) of freedom; this allows us to conclude that social right is the existence of social freedom. For common sense, social right designates the liberties conquered in the face of risks of subsistence in a capitalist market society. In my paper, I argue first that Hegel’s Philosophy of Right is a criterion for a critical analysis of modern states. Second, I show that Marx can be only rational understood if we see how his arguments follow methodologically from Hegel’s Philosophy of Right, and in order to deal with social and constitutional questions before the events of March 1848. It is through this key historical confrontation that Marx develops a principle of social rights that, on its turn, creates social freedom in the face of risks of subsistence in a capitalist market society.